Predicting the locations of possible long-lived low-mass first stars: importance of satellite dwarf galaxies - Magg, Mattis; Hartwig, Tilman; Agarwal, Bhaskar; Frebel, Anna; Glover, Simon; Griffen, Brendan F.; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. The search for metal-free stars has so far been unsuccessful, proving that if there are surviving stars from the first generation, they are rare, the
Advance access publication 2017 October 24
Gesehen am 11.09.2019